PENGARUH KONSENTRASI PUPUK ORGANIK CAIR BULU AYAM TERHADAP STATUS HARA NITROGEN DAN PERTUMBUHAN TANAMAN PAKCOY (Brassica rapa L.) DENGAN HIDROPONIK SISTEM SUMBU: The Effect of Chicken Feather Organic Liquid Fertilizer Concentration on Nitrogen Nutrient Status and Growth, Of Pakcoy Plants (Brassica rapa L.) In Hydroponic Wick System - Purtiwi, Nima; Inonu, Ismed; Prayoga, Gigih Ibnu (Enviagro: Jurnal Pertanian dan Lingkungan, 2023)
Cultivation of plants using hydroponic technology is growing along with the decreasing area of ​​agricultural land every year because it is being converted a lot. Disadvantages of hydroponic cultivation are the relatively expensive price of nutrients and the use of chemicals in nutrient solutions. Efforts that can be made are by utilizing waste chicken feathers to become liquid organic fertilizer as a substitute for inorganic nutrients. This study aims to determine the effect of giving various concentrations of liquid organic fertilizer from chicken feather waste on nitrogen (N) nutrient status, growth and yield of pakcoy plants with hydroponic wick systems. This research was conducted from November 2019 to April 2020 at the Experimental and Research Garden of the Faculty of Agriculture, Fisheries and Biology. This study used a completely randomized design (CRD) with 6 replications and 4 treatment levels of K0 (100% AB Mix), K1 (90% liquid fertilizer), K2 (70% liquid fertilizer), and K3 (50% liquid fertilizer). The results showed that the higher the concentration of chicken feather Liquid Organic Fertilizer, the amount of Ntotal in plant tissue increased. The application of liquid organic fertilizer has an effect on the growth of pakcoy plants. The application of liquid organic fertilizer has an effect on the growth of pakcoy plants. Treatment of 50% liquid fertilizer concentration resulted the best growth of pakcoy plants however lower than AB Mix nutrition.